Seed placement accuracy in cereals: Agronomic and economic capabilities of winter wheat in crop growth and yield formation at improved crop space homogeneity - Bund, Thomas; Justus Liebig University Giessen (My University, 2021)
Improving the longitudinal seed distribution of wheat seeds and the use of hybrid wheat varieties are enablers to increase wheat yields. For that reason, the effect on winter wheat yield production was tested from October 2018 until August 2020, comparing a conventional, volumetric seeder with a singulation planter at four different seed rates (80-320 seeds/m²), reflecting a hybrid and a non-hybrid wheat variety under differing climate conditions in Europe. In a technical perspective, the singulation planter improved the longitudinal plant distribution. The coefficient of variation of the plant-to-plant distances was reduced in average by 27 % while having higher amounts of plant spacings within the target range of 0.5-1.5 deviation to target mean seed distance, compared to volumetric seeding. As result, the singulation planter increased wheat yield in average by 0.48 t/ha. Beside that, the maximum wheat yield of the volumetric seeder was maintained at 50 % lower seed densities when using the singulation planter. No yield difference was observed between the non-hybrid and hybrid wheat variety. This underlined the missing economic competitiveness of the tested hybrid wheat variety, even though at low seed densities. The economic benefit of the singulation planter was with 120 €/ha greater for hybrid wheat, as result of more seed cost savings at higher yield production compared to non-hybrid wheat (+ 22€/ha). Seeding winter wheat with a singulation planter improves efficiency of plant growth, resulting in higher yields while having potential to reduce seed densities. Additional input savings in plant protection and fertilization are expected, further research needs to be investigated.
Keywords: Winter wheat; Growth space; Seeding technique; Singulation; Longitudinal plant spacing; Seed spacing quality; Cereals; ddc:630